(untitled) (Olhar de Professor, 2021)
This article presents a discussion on the importance of careful listening to children in research and the drawing as source of artistic production about their favorite play in the school routine of Children’s Education. The aim of this study is to present production of drawings made by children to represent their favorite play and discuss the importance of the play for the children’s development through theoretical foundation of historical-cultural psychology. The methodology used was qualitative research based on historical-cultural approach, chat groups were conducted and registers of the drawings made by the children about their favorite play were made. As a result, it was possible to widen concepts about the participation of the child in Children’s Education, which were analyzed based on the opinions of both the children and the adults, making it possible for the researchers to reflect on the spaces and moments dedicated to the play in the school routine of Children’s Education.